The impact of the DWI-FLAIR-mismatch in the ECASS-4 trial: a post hoc analysis - Pfaff, Johannes; Bendszus, Martin; Donnan, Geoffrey; Molina, Carlos; Leys, Didier; Schellinger, Peter D.; Schwab, Stefan; Toni, Danilo; Wahlgren, Nils; Hacke, Werner; Ringleb, Peter A. (European stroke journal, 2020)
Introduction: To investigate the impact of a mismatch between diffusion-weighted imaging (DWI) and fluid attenuated inversion recovery (FLAIR) on functional outcome in patients with acute stroke in a prolonged time window or unknown time of symptom onset randomized to intravenous thrombolysis or placebo. Patients and Methods: We performed a post-hoc analysis of the European Cooperative Acute Stroke Study-4 (ECASS-4) trial. ECASS-4 was an investigator driven, phase 3, multi-center, double-blind, placebo-controlled study which randomized ischemic stroke patients presenting within 4.5 and 9h of stroke onset or unknown time-window to either rt-PA or placebo after MR-imaging. Two subgroups "no mismatch" (nMM) and "any mismatch" (aMM) were created by applying a DWI-FLAIR-mismatch criterion. We calculated frequency of nMM and aMM and performed a univariate analysis (Fisher's Test) for excellent clinical outcome (mRS 0-1) and mortality (mRS=6). Results: MR-Imaging of n=111/119 (93.2%) patients was suitable for this analysis. DWI-FLAIR mismatch was found in 49 patients (44.1%). Proportions of mismatch nMM and aMM were comparable in treatment-groups (aMM: Placebo 46.3%, Alteplase 42.1%; p=0.70). Patients with nMM showed no benefit of rt-PA-treatment (OR (95%CI) mRS 0-1: 0.95 (0.29-3.17)). Patients with aMM showed a point estimate of the odds ratio in favour of a treatment benefit of rt-PA (mRS 0-1: OR (95%CI) 2.62 (0.68-11.1)). Mortality within 90 days was not different in patients treated with rt-PA if nMM (15.2%) or aMM (12.5%) was present. Discussion: In this analysis no significant evidence, but subtle indication towards patients treated with rt-PA in a prolonged time window reaching an excellent clinical outcome if a DWI-FLAIR-mismatch is present on initial stroke MR-imaging. Conclusion: A DWI-FLAIR mismatch in the region of ischemia as imaging based surrogate parameter for patient selection for i.v. rt-PA should be strongly pursued.
Gesehen am 13.07.2021